3D Mapping of Crystallographic Phase Distribution using Energy‐Selective Neutron Tomography. (2nd April 2014) - Woracek, Robin; Penumadu, Dayakar; Kardjilov, Nikolay; Hilger, Andre; Boin, Mirko; Banhart, John; Manke, Ingo
<x xml:space="preserve">Abstract</x> Nondestructive 3D mapping of crystallographic phases is introduced providing distribution of phase fractions within the bulk (centimeter range) of samples with micrometer‐scale resolution. The novel neutron tomography based technique overcomes critical limitations of existing techniques and offers a wide range of potential applications. It is demonstrated for steel samples exhibiting phase transformation after being subjected to tensile and torsional deformation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>